2015
DOI: 10.1074/jbc.m115.655720
|View full text |Cite|
|
Sign up to set email alerts
|

Signal Transduction by BvgS Sensor Kinase

Abstract: Background:The sensor kinase BvgS controls Bordetella virulence and is modulated by nicotinate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Transcription of bvgR is activated directly by BvgA~P binding to the promoter PbvgR (18). Somewhat atypically compared to other twocomponent sensor kinases, BvgS appears to be turned on, i.e., actively phosphorylating BvgA, in the absence of specific signals, with recent elegant biochemical, structural, and genetic studies supporting this view (19)(20)(21)(22)(23)(24)(25). However, BvgS can be turned off by addition of compounds such as MgSO 4 or nicotinic acid to the growth medium or by culture at lower temperatures (25°C), resulting in the Bvg Ϫ mode, a phenomenon known as modulation (26).…”
Section: Importancementioning
confidence: 99%
“…Transcription of bvgR is activated directly by BvgA~P binding to the promoter PbvgR (18). Somewhat atypically compared to other twocomponent sensor kinases, BvgS appears to be turned on, i.e., actively phosphorylating BvgA, in the absence of specific signals, with recent elegant biochemical, structural, and genetic studies supporting this view (19)(20)(21)(22)(23)(24)(25). However, BvgS can be turned off by addition of compounds such as MgSO 4 or nicotinic acid to the growth medium or by culture at lower temperatures (25°C), resulting in the Bvg Ϫ mode, a phenomenon known as modulation (26).…”
Section: Importancementioning
confidence: 99%
“…BvgS is in a kinase mode of activity in the basal state at 37°C. In the laboratory, the addition of modulators, such as MgSO 4 or nicotinate, or conditions of low temperature or nutrient restriction shift the bacteria to the Bvg − , avirulent phase ( 12 16 ). By using a Phos-Tag assay, we have shown that the dephosphorylation of BvgA is much faster after the addition of nicotinate to bacteria than when it occurs spontaneously, indicating that BvgS acts as a phosphatase in the Bvg − phase ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that BvgS contains three putative signal perception domains and therefore has the potential to integrate multiple distinct environmental signals has been known for 20 years (21, 37, 38). To date, however, roles only for the VFT domains have been identified (15)(16)(17). Studies investigating the purpose of the PAS domain have suggested a role only in transducing signals sensed by the VFTs to the cytoplasmic signaling domains (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Hence the "default" state for BvgS is one in which it is an active kinase. Binding of NA to VFT2 alters its conformation, and this change is apparently transduced across the membrane, which is proposed to cause reversal of the phosphorelay, resulting in the dephosphorylation of BvgA and a shift to the Bvgphase (17).…”
Section: Figmentioning
confidence: 99%